Tectonic Models of the Lesser Sunda Islands - Minarwan, Minarwan (Berita Sedimentologi, 2012)
The Lesser Sunda Islands or "Nusa Tenggara‟ as they are known in Indonesia, are a group of islands located to the immediate east of Java and to the north of Western Australia. Major islands in the group include Bali, Lombok, Sumbawa, Flores, Sumba and Timor. Most of the islands, except for Sumba and Timor, contain active volcanoes and are volcanic in origin. The volcanic islands are aligned in a W to E direction, forming the magmatic arc that constitutes the East Sunda-Banda Arc. Sumba and Timor are located to the south of the volcanic chain and they form the southern part of Banda Arc.The East Sunda Arc includes Bali, Lombok and Sumbawa. Flores, which is the next island located to the east of Sumbawa, is the beginning of the Banda Arc. The Banda Arc itself is subdivided into the volcanic inner Banda Arc that includes Flores, Alor, Wetar, and other smaller volcanic islands to the northeast of Wetar; and the non-volcanic outer Banda Arc that includes islands such as Sumba, Timor, Babar, Tanimbar and Kai. The boundary between the East Sunda and Banda Arcs coincides with a change in present-day relationship of Australia-Eurasia plates, from an oceanic subduction type to continental collision type. In the inner Banda Arc, no active volcanic activities currently exist in the Alor, Lirang and Wetar islands.This article summarizes the tectonic models of the Lesser Sunda Islands, particularly of the area between Java and the Timor islands. The summary is based on various publications of several key researchers, who have used their own findings and also those of other authors to propose their interpretation. The objective of this article is to review current understanding and interpretation of crust composition, tectonic models and arc volcanism of the region.